A pharmacological overview of lamotrigine for the treatment of epilepsy. Issue 12 (1st December 2016) - Yasam, Venkata Ramesh; Jakki, Satya Lavanya; Senthil, V.; Eswaramoorthy, M.; Shanmuganathan, S.; Arjunan, K.; Nanjan, MJ
ABSTRACT: Introduction : Epilepsy is one of the most common neurological disorders, affecting about 2% of the population worldwide. Lamotrigine (LTG) is a second generation anti-epileptic drug (AED) with broad spectrum of activity, a favourable side-effect profile, simpler dosing than earlier drugs and efficacious in diverse epilepsy syndromes. Areas covered : The present review focuses on pharmacodynamics, pharmacokinetics, clinical efficacy, safety and tolerability of LTG and its effect on cognition, psychiatry, quality of life, women and pregnancy along with effect of enzyme inducing and enzyme inhibiting drugs over LTG and their effect on serum level fluctuations by collecting data from various studies over the years until 2016. Expert commentary : Results from various studies and clinical trials indicate that LTG possessed a favourable profile of anticonvulsant activity and good tolerability as a monotherapy/or add-on therapy in children and adult patients against several types of seizures and syndromes. It has wide clinical dose range with favourable pharmacokinetic properties making it an excellent therapeutic option in epilepsy.